Estudo comparativo entre a pirólise do polietileno de baixa densidade, utilizando vermiculita modificada e SBA-15 - Bezerra, Franciel Aureliano (2014)
Catalytic processes are widely present in everyday life. This results in large number of studies seeking materials that may combine the low cost catalytic efficiency. Based on this assumption, the clays have long been used as catalysts, with its huge availability, diversity and possibility of improving their properties from structural changes, primarily responsible for this great use. Among the natural clays, vermiculite due to their characteristic properties (high cation exchange capacity and expansion), is suitable for various applications including as catalysts and catalyst supports. In this work, the acid leaching of clay vermiculite was performed, coming from Santa Luzia-PB, with nitric acid (2, 3 and 4 mol / L) and subsequent calcination of the materials obtained. The materials were named as Vx/400, where x is the acid concentration employed and 400 used in calcination temperature. The effectiveness of changes made was determined by XRD techniques, FT-IR, EDS, TG/DTG, nitrogen physisorption and DTP of n-butylamine. Acid leaching has improved some properties of the clay - specific area and acidity - but the control of the acid concentration used is of vital importance, since the highest concentration caused the partial destruction of vermiculite entailing a decline in their properties. For analysis of the catalytic activity of the modified clay was made a comparative study with the SBA -15 mesoporous materials, synthesized via hydrothermal method, using the pyrolysis of low density polyethylene (LDPE). The results showed that the acid plays a fundamental role in the conversion of the polymer into smaller molecules, the material V3/400 was more selective for the source monomer (ethylene) due to their increased acidity, which promotes more breaks bonds in the polymeric chain, while materials and V0/400 V2/400, lower acidity, showed higher selectivity to light hydrocarbons, the range of fuel (41.96 and 41.23%, respectively), due to less breakage and secondary condensation reactions chains; already V4/400 SBA-15/550 and resulted in lower percentages of light hydrocarbons and the partial destruction of the structure and low acidity, respectively, responsible for the inefficiency of materials